2001
DOI: 10.1136/bmj.323.7325.1336
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of schizophrenia in ethnic minorities in London: ecological study into interactions with environment

Abstract: Objective To determine whether the incidence of schizophrenia among people from non-white ethnic minorities is greater in neighbourhoods where they constitute a smaller proportion of the total population. Design Ecological design including retrospective study of case records to calculate the incidence of schizophrenia in the ethnic minority population across electoral wards and multi-level analysis to examine interaction between individuals and environment. Setting 15 electoral wards in Camberwell, South Londo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
308
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(345 citation statements)
references
References 17 publications
30
308
1
6
Order By: Relevance
“…Further analyses contribute to the suggestion that socio-economic risk factors may be operating not just at the level of the individual, but also at the level of the community. For example, Kirkbride et al (in press) found that risk of psychosis is highest for African-Caribbeans when they form a smaller proportion of the population, a finding that partially replicates an earlier finding by Boydell et al (2001).…”
Section: Adverse Social Experiences and Psychosis (2) ^S O P Findingssupporting
confidence: 75%
“…Further analyses contribute to the suggestion that socio-economic risk factors may be operating not just at the level of the individual, but also at the level of the community. For example, Kirkbride et al (in press) found that risk of psychosis is highest for African-Caribbeans when they form a smaller proportion of the population, a finding that partially replicates an earlier finding by Boydell et al (2001).…”
Section: Adverse Social Experiences and Psychosis (2) ^S O P Findingssupporting
confidence: 75%
“…21 Our findings suggest that there may be a common social mechanism of action through which Bethnic density,^or the relative size of ethnic groups in areas that are occupied by members of more than one group, 22 leads to a mortality benefit at the local level. Ethnic density effects for whites, blacks, and various immigrants have been described in psychiatric literature [21][22][23][24][25][26][27] in both the United Kingdom and the United States; their authors [21][22][23][24]27 have theorized that members less socially isolated or marginalized are perhaps shielded from prejudice and better positioned to access social support and community resources, thereby reducing psychiatric vulnerability. The same mechanism of action may explain the reduction in mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…This work has been conducted in Southeast London, an urban region with a large proportion of migrants, deprived areas, and a high incidence of psychosis (Boydell et al, 2001;Boydell et al, 2003). Previous studies have identified environmental risk factors for schizophrenia, like urban place of birth (Pedersen and Mortensen, 2001) and neighborhood environment (van Os et al, 2000), which support the link between a stressful environment and the development of psychosis.…”
Section: Discussionmentioning
confidence: 99%